Strategi Optimalisasi E-Government Untuk Mewujudkan Good Governance Di Kota Kediri - Nauru Rispati; Eka Askafi (Otonomi, 2023)
The development of technology progress can change the human perspective in society, to balance that, the term electronic-based government appears or in other words name (e-government). The governments who are aware the benefits of implementing e-government can support the realization of good governance. The purpose of this research is to find out the implementation of e-government in Ngronggo Village, Kecamatan Kota, Kota Kediri and to find out e-government optimization strategies to realize good governance in Ngronggo Village, Kecamatan Kota, Kota Kediri. This research was qualitative research which in a case study. The data collection methods used were interviews and focus group discussions (FGD). The data analysis methods used were reduction, data presentation and conclusion. The results of this research showed that implementation of e-government has been carried out in step by step until now. In the application of e-government, there were supporting factors liked the leadership authority who had a great influence in provide services as well and the other factors was technology expertise and technology infrastructure, and the resistor factors liked resources that were less able to used technology. Good governance in the City of Kediri is now starting to show the results, but there are still some of obstacles that must be evaluated and updated on an ongoing basis